PENGABAIAN SAKSI-SAKSI MAHKOTA OLEH HAKIM SEBAGAI DASAR KASASI PENUNTUT UMUM KEJAKSAAN NEGERI PANGKALPINANG TERHADAP PUTUSAN BEBAS PERKARA NARKOTIKA (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR: 1603 K/PID.SUS/2009) - Yosafat Agung Putra, Arini Mufidatun Deri Setiawan (GEMA, 2015)
This study aims to determine the suitability of the cassation by the public prosecutor State Attorney Pangkalpinang on the basis of a waiver of the crown witnesses by the judge against the acquittal cases Narcotics with the provisions of the Criminal Procedure Code and to determine the suitability of the Supreme Court in a legal reason to examine and decide the cassation public prosecutor State Attorney Pangkalpinang against the acquittal cases Narcotics with the provisions of the Criminal Procedure Code. This research is a normative or prescriptive doctrinal and applied by using a type of primary and secondary data. Data collection techniques used is the study of documents or library materials, namely the collection of legal materials related to the problems examined. The acquired data will be studied and analyzed appropriate by purpose and research problems.